Growth and yield of African ginger in response to application of organic fertiliser. Issue 4 (8th August 2021) - Maphothoma, Phomolo; Kleynhans, Riana; Prinsloo, Gerhard; Mokgehle, Salmina N; du Plooy, Ian; Araya, Hintsa T
Abstract : African ginger ( Siphonochilus aethiopicus ) is in high demand for medicinal use. The plant does not multiply after being harvested, as it is destroyed in the process. The species is now facing extinction as a result of over harvesting. In order to mitigate this threat, cultivation of the species has become priority. The objective of this study was to determine the growth and yield parameters of S. aethiopicus in relation to organic fertiliser treatments. The parameters were evaluated in response to three organic fertiliser applications (0, 100 and 200 kg N ha −1 ) and three rhizome sizes, namely small (10–20 g), medium (20–40 g) and large (> 40 g). The combination of a fertiliser application of 100 kg N ha −1 and large rhizomes provided the best results, with maxima for rhizome yield (7 t ha −1 ) and root yield (6 t ha −1 ). Small and medium rhizomes had a significantly lower yield than large rhizomes at all nitrogen levels. The different fertiliser applications were associated with significant variation in leaf chlorophyll content. It is concluded that the application of 100 kg N ha −1 and planting of large rhizomes would result in the best yield for African ginger's commercial production.